DETERMINATION OF THE SWITCHES TIME SERVICE - Danilenko, E. I.; Karpov, M. I.; Boiko, V. D. (Science and Transport Progress, 2003)
The technique of definition of normative service life is shown for various parameters of operational conditions depending on characteristics of force loading of a way.